KEADILAN PROSEDURAL DAN IKLIM KERJA ETIS SEBAGAI PEMODERASI PENGARUH PARTISIPASI PENGANGGARAN PADA SENJANGAN ANGGARAN (Studi Empiris Pada Pemerintah Kabupaten Tabanan) - Ariawan, Putu Pande; Wirakusuma, Made Gede; Ratnadi, Made Dwi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.07.TAHUN 2015, 2015)
The research to examine that procedural justice and ethical work climate as a moderation variabels for the effect of budgetary participation on budgetary slack. This research was conducted at 41 SKPD in Tabanan regency. The sample was taken by purposive sampling with criteria. Data collected by survey method. The respondents were 123 government officers in Tabanan regency who were involved in budgetary planning.The empirical analysis is conducted using Moderated Regression Analysis.The results of this research  that the budgetary participation give positive effect on budgetary slack. The interaction between budgetary participation and procedural justice decrease the budgetary slack, meanwhile the interaction between budgetary participation and ethical work climate increase the budgetary slack.
Keywords: procedural justice, ethical work climate, budgetary participation, budgetary slack, Tabanan regency